Liquid purification method, method for producing liquid or cleaning liquid, filter medium and filter device

By using the connecting pore structure and imide bond opening process of the pore membrane of polyimide and/or polyamideimide porous membrane, the problems of existing membranes in removing iron and zinc, flow rate and durability are solved, and the problem of the current membrane is achieved. Efficient and stable metal removal and flow rate maintenance.

CN107249720BActive Publication Date: 2025-01-10TOKYO OHKA KOGYO CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN201680011538.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2016-02-03
Filing Date
2016-02-22
Publication Date
2025-01-10
Estimated Expiration
2036-02-22

AI Technical Summary

Technical Problem

The existing porous nylon and polyethylene membranes are difficult to effectively remove contaminated metals such as iron and zinc during semiconductor manufacturing, and their removal performance is degraded and prone to rupture when the flow rate is accelerated, and their durability is insufficient.

Method used

Polyimide and/or polyamide imide porous membrane is used to allow liquid to pass through differential pressure, and the interconnected pore structure is used to achieve efficient removal of metal impurities, and the porosity of the membrane is improved through the imide bond ring opening process. and mechanical properties.

Benefits of technology

It realizes efficient removal of metals such as iron and zinc, maintains high flow rates, and improves the stress and elongation of the film, and enhances the durability of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0001386008130000091
    Figure BDA0001386008130000091
  • Figure BDA0001386008130000092
    Figure BDA0001386008130000092
  • Figure BDA0001386008130000211
    Figure BDA0001386008130000211
Patent Text Reader

Abstract

The present invention provides a method for purifying a liquid using a porous polyimide and / or polyamideimide membrane, a method for producing a liquid or a cleaning liquid using the purification method, a filter medium formed by the porous membrane, and a filter device including the porous membrane. The porous polyimide and / or polyamideimide membrane has excellent removal performance for impurities such as metals, preferably can also achieve excellent flow rate at the same time, and has excellent stress, elongation at break, etc. The present invention relates to a method for purifying a liquid, the method comprising the following steps: using differential pressure to make a part or all of the liquid pass from one side to the other side of a porous polyimide and / or polyamideimide membrane having interconnecting pores.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for purifying a liquid using a polyimide and / or polyamideimide porous membrane, a method for producing a drug solution or a cleaning liquid using the purification method, a filter medium formed from the polyimide and / or polyamideimide porous membrane, and a filter device including the polyimide and / or polyamideimide porous membrane. Background Art

[0002] As the demand for high performance, high functionality and low power consumption increases for semiconductor devices, the circuit pattern is becoming increasingly fine, and with it comes the need to remove contaminant metals that would cause a decrease in manufacturing yield. Therefore, it is desirable that chemical solutions such as chemical solutions for forming a protective film for imparting hydrophobicity to a substrate and cleaning solutions for silicon wafers do not contain contaminant metals such as iron and zinc.

[0003] The chemical solution described above used in the process of manufacturing semiconductor devices may be purified by a filtration device or the like in order to remove contaminating metals such as iron and zinc in advance. The filtration device generally has a filtration medium using a porous membrane.

[0004] In order to remove impurities such as metal ions, porous membranes that can also remove tiny substances such as nanoparticles are desirable. As a filter membrane that can remove impurities from a liquid medicine or a resin material used in applications such as semiconductor devices, nylon, polyethylene, polypropylene, PTFE, etc. are generally used. For example, it is known that organic impurities can also be removed by using a filter membrane such as nylon (for example, Patent Document 1).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent No. 4637476 Summary of the invention

[0008] Problems to be solved by the invention

[0009] However, the membrane formed of nylon has a weak acid resistance, so it is difficult to clean with acid and remove impurities mixed in or attached to the filter itself. In addition, the membrane formed of polyethylene has a low removal rate for impurities such as iron and zinc that must be removed from the chemical solution used in the semiconductor device manufacturing process.

[0010] For porous membranes that can be used for filter media, it is required in industry that they can be processed at a certain flow rate, but if the flow rate is increased, there is a tendency for the removal performance of metal and other impurities to deteriorate, and it is not easy to achieve excellent flow rate and impurity removal performance at the same time. For films formed of polyethylene, if the flow rate is increased, there is also the problem of film rupture. In addition, since filter media are repeatedly used in industry, porous membranes with durability (high stress, elongation at break, etc.) are preferred.

[0011] The present invention is made in view of the above situation, and its purpose is to provide a method for purifying a liquid using a polyimide and / or polyamide-imide porous membrane, a method for producing a drug solution or a cleaning liquid using the purification method, a filter medium formed by the porous membrane, and a filter device including the porous membrane. The polyimide and / or polyamide-imide porous membrane has excellent performance in removing impurities such as metals, preferably can also achieve excellent flow rate at the same time, and is also excellent in stress, elongation at break, etc.

[0012] Means for solving problems

[0013] The inventors of the present application discovered that a porous polyimide and / or polyamideimide membrane having interconnected pores does not impair the stress, elongation at break, etc. caused by the polyimide and / or polyamideimide, and at least through its porous structure, has excellent performance in removing impurities such as metals, and can maintain the impurity removal performance even when the flow rate is increased, thereby completing the present invention.

[0014] A first aspect of the present invention is a method for purifying a liquid, comprising the step of causing a part or all of the liquid to permeate from one side to the other side of a porous polyimide and / or polyamideimide membrane having continuous pores using a differential pressure.

[0015] A second aspect of the present invention is a method for producing a chemical solution or a cleaning solution using the liquid purification method of the first aspect of the present invention.

[0016] A third aspect of the present invention is a filter medium formed of the above-mentioned polyimide and / or polyamide-imide porous membrane used in the liquid purification method of the first aspect of the present invention.

[0017] A fourth aspect of the present invention is a filtration device including the polyimide and / or polyamide-imide porous membrane used in the liquid purification method of the first aspect of the present invention.

[0018] Effects of the Invention

[0019] The present invention can provide a method for purifying a liquid using a porous membrane of polyimide and / or polyamideimide, a method for manufacturing a drug solution or a cleaning liquid using the purification method, a filter medium formed by the porous membrane, and a filter device including the porous membrane. The porous membrane of polyimide and / or polyamideimide has excellent metal removal performance, preferably can also achieve excellent flow rate at the same time, and is also excellent in stress, elongation at break, etc. DETAILED DESCRIPTION

[0020] Hereinafter, embodiments of the present invention will be described in detail, but the present invention is not limited to the following embodiments at all and can be implemented with appropriate modifications within the scope of the purpose of the present invention.

[0021] In this specification, the description of "P and / or Q" such as "polyimide and / or polyamide-imide", and the description of "P, Q and / or R" such as "carboxyl group, salt-type carboxyl group and / or -NH- bond", respectively mean "at least one selected from the group consisting of P and Q" and "at least one selected from the group consisting of P, Q and R", and other descriptions using "and / or" also apply to this description. Here, P, Q and R are arbitrary terms.

[0022] [Liquid purification method]

[0023] A first aspect of the present invention is a method for purifying a liquid, comprising the step of causing a part or all of the liquid to permeate from one side to the other side of a porous polyimide and / or polyamide-imide membrane having continuous pores using a pressure difference.

[0024] <Polyimide and / or polyamide-imide porous film>

[0025] The polyimide and / or polyamide-imide porous membrane used in the liquid purification method of the present invention has a connected hole. The connected hole is formed by each hole (hereinafter, sometimes simply referred to as a "hole") that imparts porosity to the polyimide and / or polyamide-imide porous membrane, and the hole is preferably a hole with a curved surface on the inner surface described later, and more preferably a nearly spherical hole described later. In the polyimide and / or polyamide-imide porous membrane, the portion where the holes are formed adjacent to each other becomes a connected hole, and the hole has a structure that is interconnected. It is usually preferred that a plurality of the holes are connected to form a whole to form a flow path for the purified liquid. The "flow path" is usually formed by connecting each "hole" and / or "connected hole". Each hole can be said to be a hole formed by removing each particle present in the polyimide resin-microparticle composite membrane through a subsequent process in the method for manufacturing the polyimide resin porous membrane described later. The communicating pores may be said to be adjacent pores formed by removing the particles in a subsequent step from the contacting portions of the particles in the polyimide resin-particle composite film in the method for producing the porous polyimide resin film described below.

[0026] The polyimide and / or polyamide-imide porous membrane in the present invention preferably has the following connected pores: the connected pores having openings on the external surface of the porous membrane are connected to the inside of the porous membrane, and the external surface on the opposite side (back side) of the porous membrane also has openings, thereby ensuring the flow path of the fluid passing through the porous membrane. For example, the polyimide and / or polyamide-imide porous membrane in the present invention can be represented by Gurley air permeability, and as Gurley air permeability, for example, it can be 30 to 1000 seconds.

[0027] The Gurley air permeability of the polyimide and / or polyamide-imide porous membrane in the present invention can be, for example, within 1000 seconds, preferably within 600 seconds, more preferably within 500 seconds, and most preferably within 300 seconds. Since the lower the better, the lower limit is not particularly set, but from the perspective of efficiently carrying out metal removal and other treatments while maintaining the flow velocity of the fluid passed through the polyimide and / or polyamide-imide porous membrane to a certain degree of high value, for example, preferably more than 30 seconds. If the Gurley air permeability is within 1000 seconds, the degree of porosity is sufficiently high, therefore, the effect of the purification of the liquid in the present invention can be improved.

[0028] The polyimide and / or polyamide-imide porous membrane of the present invention preferably comprises a communicating hole with a pore size of 1 to 200 nm. The pore size of the communicating hole is preferably 3 to 180 nm, more preferably 5 to 150 nm, and further preferably 10 to 130 nm. The pore size of the communicating hole is the diameter of the communicating hole. A single communicating hole can be formed by two adjacent particles using the manufacturing method described later, so the diameter, for example, sometimes refers to the diameter in the direction perpendicular to the length direction when the two parts of each hole constituting the communicating hole are continuous as the length direction. For the pore size of the communicating hole, when the distribution of the pore size of each hole that imparts porosity to the polyimide and / or polyamide-imide porous membrane is wide, there is a tendency for the diameter of the communicating hole itself formed by each hole adjacent to each other to become smaller. In addition, from the viewpoint of reducing the pore size of the communicating hole, the porosity of the porous membrane is, for example, 60 to 90%, preferably 60 to 80%, and more preferably in the range of about 70%. In addition, when the imide bond ring-opening step described later is not performed, the pore diameter of the continuous pores tends to be small.

[0029] Since the polyimide and / or polyamide-imide porous membrane of the present invention has interconnected pores, when a fluid is passed through the porous membrane, the fluid can pass through the inside of the porous membrane. For the polyimide and / or polyamide-imide porous membrane, each pore (each pore preferably has a curved surface on the inner surface) is connected to each other through the interconnected pores to form a porous membrane. flow path Therefore, it is believed that not only can the fluid pass through the inside of the porous membrane, but also, by passing through while contacting the curved surface of each pore, the area in contact with the inner surface of the pore is increased, and tiny substances such as metal particles present in the fluid are easily adsorbed in the pores of the porous membrane.

[0030] As described above, the polyimide and / or polyamide-imide porous membrane in the present invention is preferably a porous membrane containing holes having a curved surface on the inner surface, and more preferably, most (preferably substantially all) of the holes in the porous membrane are formed by curved surfaces. In this specification, regarding a hole, "having a curved surface on the inner surface" means that at least the inner surface of the hole that brings porosity has a curved surface in at least a part of the inner surface.

[0031] For the pores in the porous membrane of the present invention, it is preferred that at least substantially all of its inner surface is a curved surface, and such pores are sometimes referred to as "nearly spherical pores" hereinafter. In this specification, the so-called "nearly spherical pores" refer to pores whose inner surface forms a nearly spherical space. Preferably, the nearly spherical pores can also be said to be pores formed when the microparticles used in the method for producing the porous membrane of the polyimide resin described later are nearly spherical. In this specification, the so-called "nearly spherical" is a concept including spheres, but it is not necessarily limited to spheres, and is a concept including substantially spherical shapes. In this specification, the so-called "substantially spherical" means that the sphericity is within 1±0.3, and the sphericity is defined as the sphericity represented by the value obtained by dividing the major diameter of the particle by the minor diameter. The nearly spherical pores possessed by the porous membrane of polyimide and / or polyamide-imide in the present invention are preferably nearly spherical pores with a sphericity within 1±0.1, and more preferably nearly spherical pores with a sphericity within 1±0.05.

[0032] By making the holes in the porous membrane have a curved surface on the inner surface, when the fluid passes through the polyimide and / or polyamide-imide porous membrane in the present invention, the fluid fully spreads throughout the inside of the holes in the porous membrane and can fully contact the inner surface of the hole. It is believed that convection may also occur along the curved surface of the inner surface depending on the situation. It is believed that in this way, tiny substances such as metal particles present in the fluid are easily adsorbed on the holes in the porous membrane in the present invention or on the recessed portion on the inner surface of the hole. The near-spherical hole may also have a recessed portion on the inner surface. The recessed portion is sometimes formed by a hole having an opening on the inner surface of the near-spherical hole and a pore size smaller than the near-spherical hole.

[0033] The polyimide and / or polyamide-imide porous membrane in the present invention can be, for example, a porous membrane having an average pore diameter of 100 to 2000 nm, preferably 200 to 1000 nm, and more preferably 300 to 900 nm. In this specification, for a porous membrane obtained by chemical etching as described later, the average pore diameter is a value obtained by calculating the average size change of the connected pores using a micropore diameter meter and calculating the actual average pore diameter from the value; for a porous membrane such as polyamide-imide that is not subjected to the above-mentioned chemical etching, the average particle diameter of the microparticles used in the manufacture of the porous membrane can be used as the average pore diameter.

[0034] The polyimide and / or polyamide-imide porous membrane of the present invention preferably comprises a structure in which nearly spherical pores having an average spherical diameter of 50 to 2000 nm are interconnected. The average spherical diameter of the nearly spherical pores is preferably 100 to 1000 nm, more preferably 200 to 800 nm. The average spherical diameter of the nearly spherical pores can be obtained by the same method as the average pore diameter in the porous membrane described above.

[0035] The polyimide and / or polyamide-imide porous film in the present invention may have a porosity of, for example, 50 to 90% by mass, and preferably 55 to 80% by mass, as determined by the method described below.

[0036] The polyimide and / or polyamide-imide porous film used in the liquid purification method of the present invention is a film containing a resin, and may be a film substantially formed only of a resin, specifically, a film containing 95% by mass or more, preferably 98% by mass or more, and more preferably 99% by mass or more of a resin. The resin contained in the polyimide and / or polyamide-imide porous film in the present invention is preferably polyimide and / or polyamide-imide, more preferably a resin containing polyimide, or may be only polyimide. In this specification, polyimide and / or polyamide-imide is sometimes referred to as "polyimide-based resin".

[0037] The polyimide and / or polyamideimide contained in the polyimide and / or polyamideimide porous film of the present invention (hereinafter, sometimes referred to as "polyimide-based resin porous film" or "porous film") may have at least one selected from the group consisting of a carboxyl group, a salt-type carboxyl group and an -NH- bond. The polyimide and / or polyamideimide preferably has a carboxyl group, a salt-type carboxyl group and / or an -NH- bond at a position other than the main chain terminal of the polyimide and / or polyamideimide.

[0038] In this specification, the so-called "salt-type carboxyl group" refers to a group obtained by replacing the hydrogen atom in the carboxyl group with a cationic component. In this specification, the so-called "cationic component" may be a cation itself in a completely ionized state, or may be a cation in a state of being ionized with -COO. - The cation constituent element may be an ion-bonded cation constituent element that is substantially uncharged, or may be an ion constituent element that is in an intermediate state between the two and has a partial charge. When the "cation component" is an M ion component formed of an n-valent metal M, the cation itself may be represented by M n+ ; As a cation component, it is "-COOM 1 / n "The element represented by "M" in ".

[0039] In the present invention, the term "cation component" may be a cation obtained by ionizing a compound listed as a compound contained in the chemical etching solution described later, and may be, typically, an ion component or an organic alkali ion component. For example, when the alkali metal ion component is a sodium ion component, the cation itself is a sodium ion (Na + ); as a cation constituent, an element represented by "Na" in "-COONa"; as a cation constituent having a partial charge, Na δ+ In the present invention, the cationic component is not particularly limited and may be an inorganic component, NH4+ 、N(CH3)4 + As inorganic components, for example, alkali metals such as Li, Na, K, alkaline earth metals such as Mg, Ca and other metal elements can be cited. Among organic components, as organic alkali ion components, NH4 + , such as NR4 + (4 R's are the same or different and represent an organic group.) A quaternary ammonium cation represented by the above organic group is preferably an alkyl group, and more preferably an alkyl group having 1 to 6 carbon atoms. Examples of the quaternary ammonium cation include N(CH3)4 + wait.

[0040] In the present invention, there is no particular limitation on the state of the "salt-type carboxyl group" and the "cationic component", which usually depends on the environment in which the polyimide and / or polyamide-imide exists, such as whether it is in an aqueous solution, in an organic solvent, or dried. In the case where the cationic component is a sodium ion component, for example, if it is in an aqueous solution, it may have dissociated into -COO - and Na + If it is in an organic solvent or has been dried, -COONa is likely not to have dissociated.

[0041] The polyimide and / or polyamide-imide in the present invention can have at least one selected from the group consisting of carboxyl, salt-type carboxyl and-NH-key, and in the case of having at least one of them, usually have carboxyl and / or salt-type carboxyl and-NH-key. In polyimide and / or polyamide-imide, with regard to carboxyl and / or salt-type carboxyl, only carboxyl can be provided, only salt-type carboxyl can be provided, and both carboxyl and salt-type carboxyl can be provided. For the ratio of carboxyl and salt-type carboxyl provided by polyimide and / or polyamide-imide, even if it is the same polyimide and / or polyamide-imide, for example, it is also possible to change according to the environment in which polyimide and / or polyamide-imide exist, and it is also possible to be affected by the concentration of cationic component.

[0042] The total number of moles of carboxyl groups and salt-type carboxyl groups in the polyimide and / or polyamide-imide of the present invention is generally equimolar to the -NH- bond in the case of polyimide. In particular, when carboxyl groups and / or salt-type carboxyl groups are formed from a part of the imide bonds in the polyimide in the method for producing a porous polyimide membrane described later, -NH- bonds are also substantially formed at the same time, and the total number of moles of the carboxyl groups and salt-type carboxyl groups formed is equimolar to the -NH- bond formed. In the case of polyamide-imide, the total number of moles of carboxyl groups and salt-type carboxyl groups in the polyamide-imide is not necessarily equimolar to the -NH- bond, but depends on the conditions of the imide bond ring-opening process such as chemical etching described later. The -NH- bond is preferably a part of an amide bond (-NH-C(=O)-).

[0043] Specifically, the polyimide and / or polyamideimide in the present invention may have at least one selected from the group consisting of structural units represented by the following formulae (3) to (6). In the case of polyimide, it may have structural units represented by the following formulae (3) and / or (4), and in the case of polyamideimide, it may have structural units represented by the following formulae (5) and / or (6).

[0044] [Chemical formula 1]

[0045]

[0046] [Chemical formula 2]

[0047]

[0048] In the above formula, X is the same or different and is a hydrogen atom or a cationic component. Ar is an aryl group and may be the same as the aryl group represented by Ar to which a carbonyl group is bonded in the repeating unit represented by the formula (1) constituting the polyamic acid described later or the repeating unit represented by the formula (2) constituting the aromatic polyimide. Y is a divalent residue obtained by removing the amino group of the diamine compound and may be the same as the aryl group represented by Ar to which N is bonded in the repeating unit represented by the formula (1) constituting the polyamic acid described later or the repeating unit represented by the formula (2) constituting the aromatic polyimide.

[0049] For the polyimide and / or polyamideimide in the present invention, a part of the imide bond ([-C(=O)]2-N-) possessed by the conventional polyimide and / or polyamideimide may be ring-opened, and in the case of polyimide, it may become a structural unit represented by the above formula (3) and / or (4), and in the case of polyamideimide, it may become a structural unit represented by the above formula (5).

[0050] However, the inventors of the present application have found that, in the case of polyamide-imide, the object of the present invention can be achieved even by having an amide bond (-NH-C(=O)-) originally possessed without ring-opening the amide bond possessed by ordinary polyamide-imide. Nevertheless, in the case of polyamide-imide, it is still preferred that a part of the amide bond originally possessed by the polyamide-imide be ring-opened to have the structural unit represented by (5) above.

[0051] For the polyimide and / or polyamide-imide in the present invention, a part of the imide bonds may be ring-opened to form a polyimide and / or polyamide-imide porous membrane having at least one selected from the group consisting of a carboxyl group, a salt-type carboxyl group and an -NH- bond. The unchanged rate when a part of the imide bonds is ring-opened is obtained as follows.

[0052] (1) For a polyimide and / or polyamide-imide porous membrane that is not subjected to the imide bond ring-opening step described later (wherein, when the varnish used to form the porous membrane contains polyamic acid, it is deemed that the imidization reaction has been substantially completed in the calcining step), the area of ​​the peak representing the imide bond measured by a Fourier transform infrared spectroscopy (FT-IR) device is divided by the area of ​​the peak representing benzene measured by the FT-IR device, thereby calculating the value (X1) represented by the obtained value.

[0053] (2) Using the same polymer (varnish) as the porous membrane for which the aforementioned value (X1) is obtained, the obtained polyimide and / or polyamide-imide porous membrane is subjected to the imide bond ring-opening step described later, and then, for the obtained polyimide and / or polyamide-imide porous membrane, the area of ​​the peak representing the imide bond measured by a Fourier transform infrared spectroscopy (FT-IR) device is divided by the area of ​​the peak representing benzene measured by the FT-IR device, thereby obtaining the value (X2) represented by the obtained value.

[0054] (3) Unchanged rate (%) = (X2) ÷ (X1) × 100

[0055] The unchanged rate of the polyimide and / or polyamide-imide porous film in the present invention is preferably 60% or more, more preferably 70% to 99.5%, and even more preferably 80 to 99%.

[0056] In the case of a porous membrane including polyamideimide, since the originally-possessing -NH- bond constituting the amide bond (-NH-C(=O)-) is included without ring-opening of the imide bond, the unchanged rate may be 100%.

[0057] In addition, when the polyimide and / or polyamide-imide porous membrane in the present invention is a polyimide porous membrane, when the value obtained by dividing the area of ​​the peak representing the imide bond measured by the Fourier transform infrared spectroscopy (FT-IR) device by the area of ​​the peak representing benzene measured by the FT-IR device is taken as the imidization rate, in the case of polyimide, (X2) in the above description is preferably 1.2 or more, more preferably 1.2 to 2, further preferably 1.3 to 1.6, further preferably 1.30 to 1.55, and particularly preferably 1.35 or more and less than 1.5. In addition, regarding the imidization rate with respect to (X1), an imidization rate of 1.5 or more is preferably adopted in the present invention. For the imidization rate, the larger the number is relatively, the more the number of imide bonds is, that is, the fewer the above-mentioned imide bonds that have been ring-opened are.

[0058] <Method for producing porous polyimide resin film>

[0059] The polyimide and / or polyamide-imide porous membrane of the present invention can be manufactured by a method including a step of forming a carboxyl group and / or a salt-type carboxyl group from a part of the imide bond in the polyimide and / or polyamide-imide (hereinafter, sometimes referred to as an "imide bond ring-opening step"). In the imide bond ring-opening step, as described above, when a carboxyl group and / or a salt-type carboxyl group is formed from a part of the imide bond, an -NH- bond that is theoretically equimolar to these groups is substantially formed at the same time. The imide bond ring-opening step is preferably performed by chemical etching described later.

[0060] However, when the resin contained in the polyimide and / or polyamideimide porous membrane is essentially formed of polyamideimide, it already has -NH- bonds even without performing the imide bond ring-opening process, and has good adsorption capacity. In addition, there is no need to particularly slow down the flow rate of the fluid. From this point of view, the imide bond ring-opening process is not necessary. However, in order to more effectively achieve the purpose of the present invention, it is preferred to perform the imide bond ring-opening process.

[0061] The method for producing a porous polyimide and / or polyamideimide film used in the present invention may include a step of forming carboxyl groups and / or salt-type carboxyl groups from a part of imide bonds in the polyimide and / or polyamideimide (imide bond ring-opening step).

[0062] As a method for producing a porous polyimide and / or polyamideimide film used in the present invention, preferably, after preparing a molded film with polyimide and / or polyamideimide as the main component (hereinafter, sometimes referred to as "polyimide and / or polyamideimide molded film".), an imide bond ring-opening step is performed. The object of the imide bond ring-opening step, i.e., the polyimide and / or polyamideimide molded film, may be porous or non-porous, and its shape is not particularly limited. From the perspective of improving the degree of porosity in the obtained polyimide and / or polyamideimide porous film, the polyimide and / or polyamideimide molded film is preferably porous, and / or, preferably, a thin shape such as a film.

[0063] As described above, the polyimide and / or polyamide-imide molded film may be non-porous when the imide bond ring-opening step is performed. In this case, it is preferable to make it porous after the imide bond ring-opening step.

[0064] As a method for making a polyimide and / or polyamideimide formed film porous, not limited to before or after the imide bond ring-opening step, a method is preferably a particle removal step that includes removing the particles from a composite film of polyimide and / or polyamideimide and particles (hereinafter sometimes referred to as a "polyimide-based resin-particle composite film") to make the film porous.

[0065] The method for producing the porous film of polyimide and / or polyamideimide used in the present invention may be (a) subjecting the composite film of polyimide and / or polyamideimide and microparticles to an imide bond ring-opening process before the microparticle removal process, or (b) subjecting the polyimide and / or polyamideimide molded film made porous by the microparticle removal process to an imide bond ring-opening process after the microparticle removal process. However, considering that the degree of porosity in the obtained polyimide and / or polyamideimide porous film can be increased, the latter method (b) is preferred.

[0066] The following describes in detail the method for producing the polyimide and / or polyamideimide porous membrane used in the present invention, mainly taking the case of using a membrane (porous membrane) as an example, which is a preferred embodiment. The membrane can be suitably produced using a varnish.

[0067] [Manufacture of varnish]

[0068] Regarding the manufacture of the varnish, the varnish can be manufactured by mixing an organic solvent in which microparticles are pre-dispersed with polyamic acid, polyimide or polyamide-imide at an arbitrary ratio, or polymerizing tetracarboxylic dianhydride and diamine in an organic solvent in which microparticles are pre-dispersed to prepare polyamic acid, or further imidizing to prepare polyimide; preferably, the final viscosity thereof is 300 to 2000 cP (0.3 to 2 Pa·s), more preferably 400 to 1800 cP (0.4 to 1.8 Pa·s). If the viscosity of the varnish is within the above range, film formation can be performed uniformly.

[0069] For the above-mentioned varnish, the resin particles can be mixed with polyamic acid or polyimide or polyamide-imide in a manner that the ratio of particles / polyimide-based resin becomes 1 to 4 (mass ratio) when the particles are fired (optionally, fired to dry) to form a polyimide-based resin-particle composite film, and the ratio of particles / polyimide-based resin is preferably 1.1 to 3.5 (mass ratio). In addition, the particles can be mixed with polyamic acid or polyimide or polyamide-imide in a manner that the volume ratio of particles / polyimide-based resin becomes 1.1 to 5 when the polyimide-based resin-particle composite film is formed. In addition, it is further preferred to make the ratio of particles / polyimide-based resin 1.1 to 4.5 (volume ratio). If the mass ratio or volume ratio of particles / polyimide-based resin is above the lower limit, pores with a density suitable for a porous membrane can be obtained. If it is below the upper limit, film formation can be stably performed without problems such as an increase in viscosity and cracking in the film. In addition, in this specification, volume % and volume ratio are values ​​at 25 degreeC.

[0070] <Microparticles>

[0071] The material of the microparticles that can be used in the present invention is not particularly limited as long as it is insoluble in the organic solvent used in the varnish and can be selectively removed after film formation. For example, as inorganic materials, metal oxides such as silicon dioxide, titanium oxide, aluminum oxide (Al2O3), and calcium carbonate can be cited; as organic materials, organic polymer microparticles (resin microparticles) such as high molecular weight olefins (polypropylene, polyethylene, etc.), polystyrene, acrylic resins (methyl methacrylate, isobutyl methacrylate, polymethyl methacrylate (PMMA)), epoxy resins, cellulose, polyvinyl alcohol, polyvinyl butyral, polyester, polyether, and polyethylene can be cited.

[0072] Preferred microparticles used in the production of polyimide resin porous membranes include silica such as colloidal silica as an inorganic material and PMMA as organic polymer microparticles, etc. Among them, spherical particles thereof are preferred because they form microscopic pores having curved surfaces on the inner surface.

[0073] As the resin particles that can be used in the present invention, for example, they can be selected from common linear polymers and known depolymerizable polymers according to the purpose without particular limitation. Common linear polymers are polymers whose molecular chains are randomly cut during thermal decomposition, and depolymerizable polymers are polymers that decompose into monomers during thermal decomposition. They can all be removed from the polyimide resin film by decomposing into monomers, low molecular weight bodies or CO2 when heated. The decomposition temperature of the resin particles used is preferably 200 to 320°C, and more preferably 230 to 260°C. If the decomposition temperature is above 200°C, film formation can be carried out even when a high boiling point solvent is used in the varnish, and the range of selection of the calcination conditions of the polyimide resin is widened. In addition, if the decomposition temperature is below 320°C, only the resin particles can be eliminated without causing thermal damage to the polyimide resin.

[0074] Among these depolymerizable polymers, homopolymers of methyl methacrylate or isobutyl methacrylate (polymethyl methacrylate or polyisobutyl methacrylate) having a low thermal decomposition temperature, or copolymers containing them as a main component are preferred from the viewpoint of the handling during pore formation.

[0075] From the aspect that the inner surface of the hole in the formed porous film is easy to have a curved surface, the microparticles that can be used in the present invention are preferably microparticles with a high sphericity. As the particle size (average diameter) of the microparticles used, for example, microparticles with a particle size (average diameter) of 50 to 2000 nm, preferably 200 to 1000 nm can be used. For the polyimide resin porous membrane obtained by removing the microparticles, when the fluid is passed as a separation material or an adsorbent, the fluid can be contacted with the inner surface of the hole in the porous membrane in the entire range, and the metal particles contained in the fluid can be efficiently adsorbed. Micro-substances such as, for example, are preferably. In addition, the particle size distribution index (d25 / 75) can be 1 to 6, preferably 1.6 to 5, and more preferably in the range of 2 to 4. By making the lower limit value above 1.6, the particles can be efficiently filled into the interior of the membrane, so it is easy to form a flow path, and the flow rate is improved, so it is preferred. In addition, it is believed that holes of different sizes are formed, and the convection mode is changed to improve the adsorption rate. However, as long as the particle size distribution index (d25 / 75) of the microparticles is above 1, even if it is lower than 1.6, the flow rate and adsorption rate are good, and the elongation at break is also easy to improve. It should be noted that d25 and d75 are the values ​​of the particle sizes at which the cumulative frequencies of the particle size distribution are 25% and 75%, respectively. In this specification, d25 refers to the larger particle size.

[0076] In addition, in the manufacturing method described later, when an unfired composite film is formed in the form of a double-layered unfired composite film, the particles (B1) used in the first varnish and the particles (B2) used in the second varnish may use the same particles, or different particles may be used. In order to make the pores on the side in contact with the substrate denser, it is preferred that the particle size distribution index of the particles (B1) is smaller than the particle size distribution index of the particles (B2), or they are the same. Alternatively, it is preferred that the sphericity of the particles (B1) is smaller than the sphericity of the particles (B2), or they are the same. In addition, it is preferred that the particle size (average diameter) of the particles (B1) is smaller than the particle size (average diameter) of the particles (B2), and it is particularly preferred to use particles with a size of 100 to 1000 nm (more preferably 100 to 600 nm) for (B1) and a size of 500 to 2000 nm (more preferably 700 to 2000 nm) for (B2). By using (B1) particles having a smaller particle size than (B2), the opening ratio of the pores on the surface of the obtained porous polyimide resin porous membrane can be made high and uniform, and the strength of the porous membrane (film) can be improved compared to the case where the entire porous polyimide resin porous membrane has the same particle size as the (B1) particles.

[0077] In the present invention, in order to make the particles in the varnish uniformly dispersed, a dispersant can be further added together with the above-mentioned particles. By adding a dispersant, polyamic acid, polyimide or polyamide-imide can be mixed with particles more evenly, and in addition, the particles in the precursor film obtained by molding or film formation can be evenly distributed. As a result, dense openings can be set on the surface of the finally obtained polyimide-based resin porous membrane, and a connected hole that efficiently connects the surface and back of the porous membrane can be formed to improve the air permeability of the polyimide-based resin porous membrane.

[0078] The dispersant that can be used in the present invention is not particularly limited, and known dispersants can be used. For example, anionic surfactants such as coconut fatty acid salts, sulfated castor oil salts, lauryl sulfate salts, polyoxyalkylene allyl phenyl ether sulfate salts, alkylbenzene sulfonic acid, alkylbenzene sulfonates, alkyl diphenyl ether disulfonates, alkyl naphthalene sulfonates, dialkyl sulfosuccinate salts, isopropyl phosphates, polyoxyethylene alkyl ether phosphate salts, polyoxyethylene allyl phenyl ether phosphate salts, etc.; cationic surfactants such as oleylamine acetate, lauryl pyridinium chloride, cetyl pyridinium chloride, lauryl trimethyl ammonium chloride, stearyl trimethyl ammonium chloride, behenyl trimethyl ammonium chloride, didecyl dimethyl ammonium chloride, etc.; and cationic surfactants such as coconut oil alkyl dimethyl amine oxide. oxide), fatty amide propyl dimethyl amine oxide, alkyl polyaminoethyl glycine hydrochloride, amido betaine type surfactant, alanine type surfactant, lauryl iminodipropionic acid and other amphoteric surfactants; polyoxyethylene octyl ether, polyoxyethylene decyl ether, polyoxyethylene lauryl ether, polyoxyethylene lauryl amine, polyoxyethylene oleyl amine (polyoxyethylene oleyl amine amine), polyoxyethylene polystyryl phenyl ether, polyoxyalkylene polystyryl phenyl ether, etc., nonionic surfactants such as polyoxyalkylene primary alkyl ethers or polyoxyalkylene secondary alkyl ethers, polyoxyethylene dilaurate, polyoxyethylene laurate, polyoxyethylated castor oil, polyoxyethylated hydrogenated castor oil, sorbitan laurate, polyoxyethylene sorbitan laurate, fatty acid diethanolamide and other polyoxyalkylene nonionic surfactants; fatty acid alkyl esters such as octyl stearate and trimethylolpropane tricaprate; polyether polyols such as polyoxyalkylene butyl ether, polyoxyalkylene oleyl ether and trimethylolpropane tri(polyoxyalkylene) ether, but not limited to these. In addition, the above dispersants can also be used in combination of two or more.

[0079] <Polyamic acid>

[0080] For the polyamic acid used in the present invention, any polyamic acid obtained by polymerizing tetracarboxylic dianhydride and diamine can be used without particular limitation. The amount of tetracarboxylic dianhydride and diamine used is not particularly limited, and it is preferred to use 0.50 to 1.50 mol of diamine, more preferably 0.60 to 1.30 mol of diamine, and particularly preferably 0.70 to 1.20 mol of diamine relative to 1 mol of tetracarboxylic dianhydride.

[0081] Tetracarboxylic dianhydride can be appropriately selected from tetracarboxylic dianhydride used as the synthetic raw material of polyamic acid in the past. Tetracarboxylic dianhydride can be aromatic tetracarboxylic dianhydride or aliphatic tetracarboxylic dianhydride. From the heat resistance of the obtained polyimide resin, aromatic tetracarboxylic dianhydride is preferably used. It is also possible to use a combination of two or more tetracarboxylic dianhydrides.

[0082] Preferred specific examples of the aromatic tetracarboxylic dianhydride include pyromellitic dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 2,2,6,6-biphenyltetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 3,3 ',4,4'-benzophenonetetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)ether dianhydride, bis(2,3-dicarboxyphenyl)ether dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 4,4-(p-phenylenedioxy)diphthalic dianhydride, 4,4-(m-phenylenedioxy)diphthalic dianhydride, 1,2,5,6-naphthalenetetracarboxylic acid dianhydride Examples of the aliphatic tetracarboxylic dianhydride include ethylene tetracarboxylic dianhydride, butane tetracarboxylic dianhydride, cyclopentane tetracarboxylic dianhydride, cyclohexane tetracarboxylic dianhydride, 1,2,4,5-cyclohexane tetracarboxylic dianhydride, 1,2,3,4-benzene tetracarboxylic dianhydride, 3,4,9,10-perylene tetracarboxylic dianhydride, 2,3,6,7-anthracene tetracarboxylic dianhydride, 1,2,7,8-phenanthrene tetracarboxylic dianhydride, 9,9-diphthalic anhydride fluorene, and 3,3',4,4'-diphenylsulfone tetracarboxylic dianhydride. Examples of the aliphatic tetracarboxylic dianhydride include ethylene tetracarboxylic dianhydride, butane tetracarboxylic dianhydride, cyclopentane tetracarboxylic dianhydride, cyclohexane tetracarboxylic dianhydride, 1,2,4,5-cyclohexane tetracarboxylic dianhydride, and 1,2,3,4-cyclohexane tetracarboxylic dianhydride. Among them, 3,3',4,4'-biphenyltetracarboxylic dianhydride and pyromellitic dianhydride are preferred in view of price, availability, etc. In addition, these tetracarboxylic dianhydrides may be used alone or in combination of two or more.

[0083] The diamine can be appropriately selected from the diamines used as the synthetic raw materials of polyamic acid in the past. The diamine can be an aromatic diamine or an aliphatic diamine. From the heat resistance of the obtained polyimide resin, an aromatic diamine is preferred. These diamines can be used in combination of two or more.

[0084] Examples of the aromatic diamine include diamino compounds to which 1 or 2 to 10 phenyl groups are bonded, specifically phenylenediamine and its derivatives, diaminobiphenyl compounds and their derivatives, diaminodiphenyl compounds and their derivatives, diaminotriphenyl compounds and their derivatives, diaminonaphthalene and its derivatives, aminophenylaminoindanes and their derivatives, diaminotetraphenyl compounds and their derivatives, diaminohexaphenyl compounds and their derivatives, and Cardo-type fluorenediamine derivatives.

[0085] Phenylenediamine includes m-phenylenediamine, p-phenylenediamine and the like. Phenylenediamine derivatives include diamines to which an alkyl group such as a methyl group or an ethyl group is bonded, and examples thereof include 2,4-diaminotoluene and 2,4-triphenylenediamine.

[0086] The diaminobiphenyl compound is a compound in which two aminophenyl groups are bonded to each other via the phenyl groups, and examples thereof include 4,4'-diaminobiphenyl and 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl.

[0087] The diaminodiphenyl compound is a compound in which the phenyl groups of two aminophenyl groups are bonded to each other via other groups. The bond is an ether bond, a sulfonyl bond, a thioether bond, a bond based on an alkylene group or a derivative group thereof, an imino bond, an azo bond, a phosphine oxide bond, an amide bond, a urea bond, etc. The alkylene bond is a bond having about 1 to 6 carbon atoms, and its derivative group is a group obtained by replacing one or more hydrogen atoms in the alkylene group with a halogen atom or the like.

[0088] Examples of the diaminodiphenyl compound include 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl ketone, 3,4'-diaminodiphenyl ketone, 2,2-bis(p-aminophenyl)propane, 2,2'-bis(p-aminophenyl)hexafluoropropane, 4-methyl-2,4-bis(p-aminophenyl)-1-pentene, 4-methyl-2,4-bis(p-aminophenyl)-1-pentene, and 4-methyl-2,4-bis(p-aminophenyl)-1-pentene. Bis(p-aminophenyl)-2-pentene, iminodiphenylamine, 4-methyl-2,4-bis(p-aminophenyl)pentane, bis(p-aminophenyl)phosphine oxide, 4,4'-diaminoazobenzene, 4,4'-diaminodiphenyl urea, 4,4'-diaminodiphenylamide, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, and the like.

[0089] Among them, p-phenylenediamine, m-phenylenediamine, 2,4-diaminotoluene, and 4,4'-diaminodiphenyl ether are preferred in view of price, availability, and the like.

[0090] The diaminotriphenyl compound is a compound in which two aminophenyl groups and one phenylene group are bonded via other groups, and the other groups can be selected from the same groups as those described for the diaminodiphenyl compound. Examples of the diaminotriphenyl compound include 1,3-bis(m-aminophenoxy)benzene, 1,3-bis(p-aminophenoxy)benzene, 1,4-bis(p-aminophenoxy)benzene, and the like.

[0091] Examples of diaminonaphthalene include 1,5-diaminonaphthalene and 2,6-diaminonaphthalene.

[0092] Examples of aminophenylaminoindan include 5- or 6-amino-1-(p-aminophenyl)-1,3,3-trimethylindan.

[0093] Examples of the diaminotetraphenyl compound include 4,4'-bis(p-aminophenoxy)biphenyl, 2,2'-bis[4-(4'-aminophenoxy)phenyl]propane, 2,2'-bis[4-(4'-aminophenoxy)biphenyl]propane, and 2,2'-bis[p-(m-aminophenoxy)phenyl]benzophenone.

[0094] Examples of the Cardo-type fluorene diamine derivative include 9,9-dianiline fluorene and the like.

[0095] The aliphatic diamine may be, for example, an aliphatic diamine having about 2 to 15 carbon atoms, and specific examples thereof include pentamethylenediamine, hexamethylenediamine, and heptamethylenediamine.

[0096] In addition, the compound in which the hydrogen atom of these diamines is substituted with at least one substituent selected from the group consisting of a halogen atom, a methyl group, a methoxy group, a cyano group, a phenyl group, etc. may be sufficient.

[0097] The method for producing the polyamic acid used in the present invention is not particularly limited, and for example, a known method such as a method of reacting an acid and a diamine component in an organic solvent can be used.

[0098] The reaction of tetracarboxylic dianhydride and diamine can usually be carried out in an organic solvent. The organic solvent that can be used in the reaction of tetracarboxylic dianhydride and diamine is not particularly limited as long as it can dissolve tetracarboxylic dianhydride and diamine and does not react with tetracarboxylic dianhydride and diamine. The organic solvent can be used alone or in combination of two or more.

[0099] Examples of organic solvents used in the reaction of tetracarboxylic dianhydride and diamine include nitrogen-containing polar solvents such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-diethylacetamide, N,N-dimethylformamide, N,N-diethylformamide, N-methylcaprolactam, and N,N,N',N'-tetramethylurea; lactone-based polar solvents such as β-propiolactone, γ-butyrolactone, γ-valerolactone, δ-valerolactone, γ-caprolactone, and ε-caprolactone; dimethyl sulfoxide; acetonitrile; fatty acid esters such as ethyl lactate and butyl lactate; ethers such as diethylene glycol dimethyl ether, diethylene glycol diethyl ether, dioxane, tetrahydrofuran, methyl cellosolve acetate, and ethyl cellosolve acetate; and phenolic solvents such as cresols. These organic solvents may be used alone or in combination of two or more. Among them, a combination of the aforementioned nitrogen-containing polar solvent and a lactone-based polar solvent is preferred. The amount of the organic solvent used is not particularly limited, but it is preferred that the content of the generated polyamic acid be 5 to 50% by mass.

[0100] Among these organic solvents, from the solubility of the generated polyamic acid, preferred are nitrogen-containing polar solvents such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-diethylacetamide, N,N-dimethylformamide, N,N-diethylformamide, N-methylcaprolactam, N,N,N',N'-tetramethylurea. In addition, from the viewpoint of film-forming properties, etc., a mixed solvent containing a lactone-based polar solvent such as γ-butyrolactone may be added, preferably 1 to 20% by mass, more preferably 5 to 15% by mass relative to the entire organic solvent.

[0101] The polymerization temperature is usually -10 to 120°C, preferably 5 to 30°C. The polymerization time varies depending on the composition of the raw materials used, but is usually 3 to 24 hours. In addition, the intrinsic viscosity of the polyamic acid solution obtained under such conditions is preferably 1000 to 100000 cP (centipoise), and more preferably in the range of 5000 to 70000 cP.

[0102] <Polyimide>

[0103] The polyimide used in the present invention is not limited in structure and molecular weight as long as it is soluble in the organic solvent used in the varnish of the present invention, and a known polyimide can be used. The polyimide may have a functional group capable of condensation such as a carboxyl group on the side chain or a functional group that promotes a crosslinking reaction during firing.

[0104] In order to form a polyimide soluble in an organic solvent, it is effective to use a monomer for introducing a soft curved structure into the main chain, for example, aliphatic diamines such as ethylenediamine, hexamethylenediamine, 1,4-diaminocyclohexane, 1,3-diaminocyclohexane, and 4,4'-diaminodicyclohexylmethane; aromatic diamines such as 2-methyl-1,4-phenylenediamine, o-tolidine, m-tolidine, 3,3'-dimethoxybenzidine, and 4,4'-diaminobenzanilide; polyoxyalkylene diamines such as polyoxyethylene diamine, polyoxypropylene diamine, and polyoxybutylene diamine; polysiloxane diamine; 2,3,3',4'-oxydiphthalic anhydride, 3,4,3',4'-oxydiphthalic anhydride, 2,2-bis(4-hydroxyphenyl)propane dibenzoate-3,3',4,4'-tetracarboxylic dianhydride, and the like. In addition, it is also effective to use a monomer having a functional group that improves solubility in an organic solvent, for example, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 2-trifluoromethyl-1,4-phenylenediamine and other fluorinated diamines. In addition, in addition to the above-mentioned monomers for improving the solubility of the polyimide, the same monomers as those described in the above-mentioned <polyamic acid> column can also be used within the range that does not hinder solubility.

[0105] There is no particular restriction on the method for manufacturing the polyimide soluble in an organic solvent used in the present invention. For example, the following known methods can be used: a method of chemically imidizing or thermally imidizing a polyamic acid so as to dissolve it in an organic solvent, etc. As such a polyimide, aliphatic polyimide (all-aliphatic polyimide), aromatic polyimide, etc. can be cited, preferably aromatic polyimide. As an aromatic polyimide, it can be a product obtained by subjecting a polyamic acid having a repeating unit represented by formula (1) to a thermal or chemical ring-closure reaction, or a product obtained by dissolving a polyimide having a repeating unit represented by formula (2) in a solvent. In the formula, Ar represents an aromatic group.

[0106] [Chemical formula 3]

[0107]

[0108] [Chemical formula 4]

[0109]

[0110] <Polyamide-imide>

[0111] The polyamideimide used in the present invention has no limitation on structure and molecular weight as long as it is soluble in the organic solvent used in the varnish of the present invention, and known polyamideimides can be used. The polyamideimide may have a functional group capable of condensation such as a carboxyl group on the side chain or a functional group that promotes a crosslinking reaction during firing.

[0112] The polyamideimide used in the present invention may be any polyamideimide obtained by reacting any trimellitic anhydride with diisocyanate or any polyamideimide obtained by imidizing a precursor polymer obtained by reacting any reactive derivative of trimellitic anhydride with diamine without particular limitation.

[0113] Examples of the above-mentioned optional trimellitic anhydride or a reactive derivative thereof include trimellitic anhydride, trimellitic anhydride halides such as trimellitic anhydride chloride, and trimellitic anhydride esters.

[0114] Examples of the above-mentioned arbitrary diisocyanates include m-phenylene diisocyanate, p-phenylene diisocyanate, o-tolidine diisocyanate, p-phenylene diisocyanate, m-phenylene diisocyanate, 4,4'-oxybis(phenylisocyanate), 4,4'-diisocyanate diphenylmethane, bis[4-(4-isocyanate phenoxy)phenyl]sulfone, 2,2'-bis[4-(4-isocyanate phenoxy)phenyl]propane, 2,4- Toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, 3,3'-dimethyldiphenyl-4,4'-diisocyanate, 3,3'-diethyldiphenyl-4,4'-diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, m-xylylene diisocyanate, p-xylylene diisocyanate, naphthalene diisocyanate, and the like.

[0115] Examples of the optional diamine include the same diamines as those exemplified in the description of the polyamic acid.

[0116] <Organic Solvents>

[0117] The organic solvent that can be used in the varnish is not particularly limited as long as it can dissolve the polyamic acid and / or polyimide resin and does not dissolve the microparticles, and can include organic solvents exemplified as solvents used in the reaction of tetracarboxylic dianhydride and diamine. The solvent can be used alone or in combination of two or more.

[0118] The content of the mixed solvent (S) in all components of the varnish is preferably 50 to 95% by mass, more preferably 60 to 85% by mass. The solid content concentration in the varnish is preferably 5 to 50% by mass, more preferably 15 to 40% by mass.

[0119] In the manufacturing method described below, when the unfired composite film is formed in the form of a double-layered unfired composite film, the volume ratio of the polyamic acid, polyimide or polyamide-imide (A1) to the microparticles (B1) in the first varnish is preferably 19:81 to 45:65. When the volume of the microparticles is 65 or more, the particles are uniformly dispersed, and when the volume of the microparticles is within 81, the particles are dispersed without agglomeration, so that holes can be uniformly formed on the substrate side of the polyimide resin molded film. In addition, the volume ratio of the polyamic acid, polyimide or polyamide-imide (A2) to the microparticles (B2) in the second varnish is preferably 20:80 to 50:50. When the whole is taken as 100, if the volume of the particles is 50 or more, the particle monomers are evenly dispersed. In addition, if the volume of the particles is within 80, the particles will not agglomerate with each other, and cracks will not occur on the surface. Therefore, a polyimide resin porous membrane with good mechanical properties such as stress and elongation at break can be stably formed.

[0120] For the above-mentioned volume ratio, the second varnish is preferably a varnish having a particle content ratio lower than that of the above-mentioned first varnish. By satisfying the above-mentioned conditions, even if particles are highly filled in polyamic acid, polyimide or polyamide-imide, the strength and flexibility of the unfired composite film, polyimide resin-particle composite film, and polyimide resin porous film can be ensured. In addition, by providing a layer with a low particle content ratio, a reduction in manufacturing cost can be achieved.

[0121] In addition to the above-mentioned components, known components such as antistatic agents, flame retardants, chemical imidization agents, condensation agents, release agents, surface conditioners, etc. may be appropriately contained as needed for the purposes of antistatic, imparting flame retardancy, low-temperature sintering, releasability, coating properties, etc.

[0122] [Manufacturing of unfired composite film]

[0123] Regarding the molding of the unfired composite film containing polyamic acid or polyimide resin and microparticles, when forming the film, the above-mentioned varnish is applied to the substrate, and the film is dried at 0 to 120°C (preferably 0 to 100°C) under normal pressure or vacuum, more preferably at 60 to 95°C (further preferably 65 to 90°C) under normal pressure. The coating film thickness is, for example, 1 to 500 μm, preferably 5 to 50 μm. It should be noted that, as required, a release layer can be provided on the substrate. In addition, in the manufacture of the unfired composite film, before the manufacture (firing process) of the polyimide resin-microparticle composite film described later, an immersion process of immersing in a solvent containing water, a pressurizing process, and a drying process after the immersion process can be provided as optional processes.

[0124] The above-mentioned release layer can be made by applying a release agent on the substrate and drying or sintering. For the release agent used herein, known release agents such as alkyl phosphate ammonium salt system, fluorine system or silicone can be used without particular restriction. When the above-mentioned dried unfired composite film containing polyamic acid or polyimide resin and particulate is peeled off from the substrate, a slight release agent will remain on the peeling surface of the unfired composite film. The residual release agent may affect the wettability of the polyimide resin porous membrane surface, the mixing of impurities, and is therefore preferably removed.

[0125] Therefore, it is preferred to use an organic solvent or the like to clean the unfired composite film peeled off from the above-mentioned substrate. As a cleaning method, it can be selected from known methods such as a method of immersing the unfired composite film in a cleaning solution and then taking it out, a method of performing spray cleaning, etc. In addition, in order to dry the cleaned unfired composite film, the following known methods can be applied without restriction: air drying the cleaned unfired composite film at room temperature; heating to an appropriate set temperature in a thermostatic bath, etc. For example, a method of fixing the end of the unfired composite film to a SUS mold frame, etc. to prevent deformation can also be adopted.

[0126] On the other hand, when the substrate is used directly without providing a release layer during the formation of the unfired composite film, the step of forming the release layer and the step of washing the unfired composite film can be omitted.

[0127] In addition, when forming a double-layer unfired composite film, first, the above-mentioned first varnish is directly applied on a substrate such as a glass substrate, and dried at 0 to 120°C (preferably 0 to 90°C) under normal pressure or in vacuum, more preferably at 10 to 100°C (further preferably 10 to 90°C) under normal pressure, to form a first unfired composite film with a film thickness of 1 to 5 μm.

[0128] Next, the above-mentioned second varnish is applied on the formed first unfired composite film, and the same operation is performed to dry it at 0 to 80°C (preferably 0 to 50°C), more preferably at 10 to 80°C (further preferably 10 to 30°C) under normal pressure, thereby forming a second unfired composite film with a film thickness of 5 to 50 μm, thereby obtaining a double-layer unfired composite film.

[0129] [Production of polyimide resin-microparticle composite film (calcination step)]

[0130] The above-mentioned unfired composite film after drying (or the unfired composite film of double layer, also hereinafter) can be subjected to post-treatment (firing) based on heating, thereby forming a composite film (polyimide resin-microparticle composite film) comprising polyimide resin and microparticles. In the case of including polyamic acid in varnish, it is preferred to complete imidization in the firing process. It should be noted that the firing process is an optional process. In particular, in the case of using polyimide or polyamide-imide in varnish, the firing process may not be performed.

[0131] The calcination temperature also varies depending on the structure of the polyamic acid or polyimide resin contained in the uncalcined composite film and the presence or absence of a condensation agent, but is preferably 120 to 400°C, more preferably 150 to 375°C.

[0132] When calcining is to be performed, the process does not necessarily need to be clearly distinguished from the drying process. For example, when calcining is performed at 375°C, the following methods can also be used: a method of heating from room temperature to 375°C over 3 hours and then maintaining at 375°C for 20 minutes; a stepwise drying-thermal imidization method of heating from room temperature to 375°C in steps of 50°C each time (maintaining for 20 minutes at each step) and finally maintaining at 375°C for 20 minutes. At this time, a method of fixing the end of the uncalcined composite film in a SUS mold frame or the like to prevent deformation can be used.

[0133] The thickness of the polyimide resin-microparticle composite membrane can be obtained by measuring the thickness at multiple locations with a micrometer or the like and finding the average value in the case of a membrane. The preferred average thickness varies depending on the use of the polyimide resin-microparticle composite membrane or the polyimide resin porous membrane. For example, when used as a separation material, an adsorption material, etc., the thickness is preferably thin, for example, 1 μm or more, preferably 5 to 500 μm, and more preferably 8 to 100 μm.

[0134] [Microparticle Removal Step (Making the Polyimide Resin-Microparticle Composite Film Porous)]

[0135] By selecting an appropriate method to remove particles from the polyimide resin-particle composite film, a polyimide resin porous film with micropores can be manufactured with good reproducibility. For example, when silicon dioxide is used as the particle, the silicon dioxide is dissolved and removed by using a low concentration of hydrogen fluoride aqueous solution (HF), etc., so that the polyimide resin-particle composite film can be made porous. In addition, when the particles are resin particles, they can be heated to a temperature above the thermal decomposition temperature of the above-mentioned resin particles and below the thermal decomposition temperature of the polyimide resin, so that the resin particles are decomposed and removed.

[0136] [Imido bond ring-opening step]

[0137] The method for producing a porous polyimide resin film in the present invention may include an imide bond ring-opening step as described above. Specifically, it may be carried out by a method including the following steps: (a) performing an imide bond ring-opening step on a polyimide resin-microparticle composite film before a microparticle removal step; or (b) performing an imide bond ring-opening step on a polyimide resin molded film that has been made porous by the microparticle removal step. As the above-mentioned production method, although even the former method (a) can open the imide bonds existing on the outer surface and the vicinity of the polyimide resin molded film to achieve the purpose of the present invention, the latter method (b) is preferred from the aspect of increasing the degree of porosity in the obtained porous polyimide resin film.

[0138] The imide bond ring-opening step can be performed by chemical etching or physical removal, or a combination of these methods. The chemical etching method is not particularly limited, and for example, a conventionally known method can be used.

[0139] As the chemical etching method, treatment using a chemical etching solution such as an inorganic alkaline solution or an organic alkaline solution can be cited. An inorganic alkaline solution is preferred. As the inorganic alkaline solution, for example, a hydrazine solution containing hydrazine hydrate and ethylenediamine, a solution of an alkali metal hydroxide such as potassium hydroxide, sodium hydroxide, sodium carbonate, sodium silicate, sodium metasilicate, an ammonia solution, an etching solution with alkaline hydroxide, hydrazine and 1,3-dimethyl-2-imidazolidinone as main components, etc. can be cited. As the organic alkaline solution, primary amines such as ethylamine and n-propylamine; secondary amines such as diethylamine and di-n-butylamine; tertiary amines such as triethylamine and methyldiethylamine; alcohol amines such as dimethylethanolamine and triethanolamine; quaternary ammonium salts such as tetramethylammonium hydroxide and tetraethylammonium hydroxide; alkaline solutions such as cyclic amines such as pyrrole and piperidine can be cited.

[0140] The solvent of each of the above solutions can be appropriately selected from pure water and alcohols. Alternatively, a solution to which an appropriate amount of a surfactant is added can be used. The alkali concentration is, for example, 0.01 to 20% by mass.

[0141] In addition, as a physical method, for example, dry etching using plasma (oxygen, argon, etc.), corona discharge, etc. can be used.

[0142] The above method can be applied to the imide bond opening step before or after the particle removal step, and thus the above method is preferred. It should be noted that when chemical etching is performed after the particle removal step, interconnected pores are easily formed inside the polyimide resin porous membrane, which can increase the porosity.

[0143] When chemical etching is performed as the imide bond opening step, a washing step of the porous polyimide resin membrane may be performed again in order to remove excess etching solution components.

[0144] As the cleaning after chemical etching, water cleaning alone may be used, but a combination of acid cleaning and / or water cleaning is preferred.

[0145] In addition, in order to improve the wettability of the surface of the polyimide resin porous membrane with respect to the organic solvent and remove the residual organic matter, the polyimide resin porous membrane may be subjected to a re-firing step. The firing conditions may be appropriately set in the same manner as the firing conditions in [Manufacturing of polyimide resin-microparticle composite membrane (firing step)].

[0146] [Specific purification method of liquid]

[0147] The method for purifying a liquid of the present invention comprises the step of causing a part or all of the liquid to permeate from one side to the other side of the above-mentioned polyimide and / or polyamide-imide porous membrane by utilizing differential pressure.

[0148] In the method for purifying a liquid of the present invention, as a method for allowing a part or all of the liquid to pass from one side to the other side of the above-mentioned polyimide-based resin porous membrane, it can usually be carried out by the following method: using the polyimide-based resin porous membrane as a separation material or adsorption material, a part or all of the liquid is filtered. The polyimide-based resin porous membrane used as a separation material or adsorption material can also be assembled into a filtering device described later.

[0149] Regarding the form of using the polyimide resin porous membrane in the liquid purification method of the present invention, a pipe-like shape formed by closing the opposite sides of a plane or polyimide resin porous membrane can be cited. When the tubular polyimide resin porous membrane is further formed into a pleated shape, the area in contact with the supply liquid increases, so it is preferred. For the polyimide resin porous membrane, as described later, in order to prevent the supply liquid from mixing with the filtrate, a sealing treatment can be appropriately implemented.

[0150] Although the purification of the liquid can also be carried out without differential pressure (i.e., by natural filtration based on gravity) using the above-mentioned polyimide-based resin porous membrane, it is preferably carried out using differential pressure. As the differential pressure, there is no particular limitation as long as a pressure difference can be set between one side and the other side of the polyimide-based resin porous membrane. Generally, there can be cited pressurization (positive pressure) in which pressure is applied to one side (supply liquid side) of the polyimide-based resin porous membrane, decompression (negative pressure) in which one side (filtrate side) of the polyimide-based resin porous membrane becomes negative pressure, etc., preferably pressurization.

[0151] Pressurization is an operation of applying pressure to one side (supply liquid side) of the polyimide resin porous membrane where there is liquid (sometimes referred to as "supply liquid" in this specification) before it passes through the polyimide resin porous membrane. For example, it is preferred to apply pressure by the following methods: using the liquid flow pressure generated by the circulation or liquid delivery of the supply liquid; or using the positive pressure of the gas. The liquid flow pressure can be generated, for example, by an active liquid flow pressure application method such as a pump (liquid delivery pump, circulation pump, etc.). Specifically, rotary pumps, diaphragm pumps, metering pumps, chemical pumps, plunger pumps, bellows pumps, gear pumps, vacuum pumps, air pumps, liquid pumps, etc. can be cited. As the liquid flow pressure, for example, it can be the pressure applied to the polyimide resin porous membrane by the liquid when the liquid passes through the polyimide resin porous membrane only by gravity, but it is preferred to apply pressure by the above-mentioned active liquid flow pressure application method. As the gas used for pressurization, it is preferred that the gas is inactive or non-reactive relative to the supply liquid, and specifically, rare gases such as nitrogen, helium, and argon can be cited. In the manufacturing field of electronic materials, especially semiconductors, pressurization is preferred. In this case, the side where the liquid that has passed through the polyimide resin porous membrane is collected is preferably atmospheric pressure that is not reduced pressure, and as pressurization, positive pressure based on gas is preferred. It should be noted that in the above pressurization method, a valve such as a pressurization valve or a three-way valve can be used.

[0152] The reduced pressure is a method of reducing the pressure on the side (filtrate side) where the liquid permeated through the polyimide resin porous membrane is collected. For example, the reduced pressure may be performed using a pump, and the reduced pressure is preferably reduced to a vacuum.

[0153] When the supply liquid is circulated or sent by a pump, the pump is usually arranged between the supply liquid tank (or circulation tank) and the polyimide-based resin porous membrane.

[0154] Pressurization may also be a method utilizing both liquid flow pressure and positive pressure of gas. In addition, for differential pressure, pressurization and decompression may be combined, for example, a method utilizing both liquid flow pressure and decompression, a method utilizing positive pressure of gas and decompression, or a method utilizing liquid flow pressure and positive pressure of gas and decompression. When combining methods for setting differential pressure, a combination of liquid flow pressure and positive pressure of gas, or a combination of liquid flow pressure and decompression is preferred from the perspective of simplicity of manufacturing. In the present invention, since a polyimide-based resin porous membrane is used, as a method for setting differential pressure, for example, even a method based on positive pressure of gas can perform purification with excellent impurity removal performance.

[0155] The pressure difference given to the front and back of the polyimide resin porous membrane by setting the differential pressure can be appropriately set according to the film thickness, porosity or average pore size of the polyimide resin porous membrane used, or the desired purity, flow rate, flow rate, or concentration or viscosity of the supply liquid, for example, in the case of the so-called cross flow mode (making the supply liquid flow in parallel with the polyimide resin porous membrane), for example, 3MPa or less, in the case of the so-called dead end mode (making the supply liquid flow in a manner intersecting with the polyimide resin porous membrane), for example, 1MPa or less. The lower limit is not particularly limited, for example, 10Pa.

[0156] In the method for purifying a liquid of the present invention, when part or all of the liquid is allowed to permeate from one side to the other side of the polyimide resin porous membrane, if the liquid contains a solute, the feed liquid may be appropriately diluted with a diluent.

[0157] In the liquid purification method of the present invention, in order to improve the wettability of the polyimide resin porous membrane with respect to the cleaning or supply liquid or adjust the surface energy between the polyimide resin porous membrane and the supply liquid, before allowing the supply liquid to pass through, a solution such as an alcohol such as methanol, ethanol, isopropanol, or a ketone such as acetone, methyl ethyl ketone, water, a solvent contained in the supply liquid, or a mixture thereof can be brought into contact with the polyimide resin porous membrane and allowed to pass through.

[0158] In the contact between the above-mentioned solution and the porous polyimide resin membrane before the supply liquid is passed through, the porous polyimide resin membrane can be impregnated or immersed in the above-mentioned solution, and by contacting the porous polyimide resin membrane with the solution, for example, the solution can also be made to penetrate into the pores inside the porous polyimide resin membrane. The contact between the above-mentioned solution and the porous polyimide resin membrane before the supply liquid is passed through can be performed by the above-mentioned differential pressure, and in particular, when the solution is also allowed to penetrate into the pores inside the porous polyimide resin membrane, it can be performed under pressure.

[0159] The polyimide resin porous membrane in the present invention is a porous membrane having polyimide and / or polyamide-imide as the main component which may have at least one selected from the group consisting of a carboxyl group, a salt-type carboxyl group and an -NH- bond. As described above, since it is a porous membrane with a high degree of porosity, it can be suitably used as a separation material and an adsorption material. The polyimide resin porous membrane in the present invention is a porous membrane having interconnected pores. As described above, it is preferably a porous membrane having interconnected pores formed by pores having curved surfaces on the inner surface, and more preferably a porous membrane having interconnected pores having a structure in which nearly spherical pores are interconnected. Therefore, when a liquid is allowed to pass through the porous membrane, part or all of the impurities containing elements that are solid at room temperature contained in the liquid can be removed from the liquid.

[0160] In this specification, the term "solid element at room temperature" refers to an element that constitutes a simple substance that is solid at room temperature (e.g., room temperature, specifically, 20°C). For example, when the element is Fe, the simple substance of the Fe element, that is, iron as a metal, is solid at room temperature, and therefore, it belongs to the "solid element at room temperature" in the present invention. As for the "solid element at room temperature", metal elements, semi-metal elements, and some non-metal elements can be generally cited. As metal elements, for example, alkali metals such as Li, Na, and K; alkaline earth metals such as Be, Mg, Ca, and Ba; transition metals belonging to Groups 3 to 11 of the periodic table such as Cr, Mn, Fe, Co, Ni, Cu, and Zn; metals belonging to Groups 12 to 15 of the periodic table such as Zn, Al, Ga, and Sn, etc. As semi-metal elements, for example, B, Si, Ge, As, Sb, Te, and Po, etc. can be cited. As some non-metal elements, C, P, S, and I, etc. can be cited. In the present invention, the “element that is solid at room temperature” is preferably a metal element or a semi-metal element, more preferably a metal element, and still more preferably iron and / or zinc.

[0161] In this specification, the so-called "impurities containing elements that are solid at room temperature" means impurities containing the above-mentioned "elements that are solid at room temperature", and may be a single substance of the element or a compound composed of a plurality of elements including the element.

[0162] For example, in the manufacturing field of electronic materials such as semiconductors, the liquid purification method of the present invention can be particularly suitably applied when the above-mentioned impurities are metal impurities containing metal elements, considering the high demand for removal from the liquid, etc. It is believed that in the present invention, by using a polyimide-based resin porous membrane, tiny substances such as metal particles present in the liquid before treatment are easily adsorbed on the holes and / or connected holes possessed by the porous membrane. The polyimide-based resin porous membrane in the present invention can also further have at least one selected from the group consisting of a carboxyl group, a salt-type carboxyl group and an -NH- bond. It is believed that by the charge or Coulomb force possessed by these groups, it is easy to attract metal particles contained in the fluid, such as metal ions, metal aggregates (for example, aggregates of metal oxides, aggregates of metals and organic matter), which can promote the adsorption of holes in the porous membrane and / or the porous membrane. In addition, it is believed that it can also function as an ion exchange membrane.

[0163] In the liquid purification method of the present invention, as described above, the polyimide resin porous membrane is a porous membrane with a high degree of porosity and interconnected pores, so it is believed that by separation and / or adsorption, part or all of the impurities containing elements that are solid at room temperature can be removed from the liquid before treatment. In this specification, the so-called "separation" may include at least one selected from the group consisting of filtration, separation, removal, capture, purification and screening, for example, it can also be applied to drainage treatment. For the liquid purification method of the present invention, by allowing micro-substances to be adsorbed on the pores and / or interconnected pores of the polyimide resin porous membrane, it can also be suitably used for separation and adsorption, such as a process of separating the micro-substance from a liquid containing the micro-substance.

[0164] As described above, the polyimide resin porous membrane in the present invention is a porous membrane containing holes with an average pore size preferably in the hundreds of nanometers, so that, for example, microscopic substances in the nanometers can also be adsorbed or captured in the holes and / or interconnected holes in the porous membrane. Therefore, the liquid purification method of the present invention using the polyimide resin porous membrane can also be suitably applied to electronic materials that require very fine impurity removal, especially in the field of semiconductor manufacturing, for example, it can be suitably applied to various purification methods for separating and / or adsorbing impurities from various liquids such as liquids or cleaning liquids used in semiconductor manufacturing. Such liquids or cleaning liquids are not particularly limited, and impurities such as iron, zinc and other contaminating metals contained in liquids such as liquids for forming protective films for modifying substrates, cleaning liquids for silicon wafers, liquids containing photosensitive materials such as resist compositions, and raw liquids of photosensitive materials such as resin solutions can be removed at a very high removal rate.

[0165] In the liquid purification method of the present invention, the polyimide resin porous membrane can be used as a filter material such as a filter medium, and specifically, it can be used alone, or it can be used as a filter material and provided with other functional layers (membranes). In addition, it can be used as a membrane combined with other filter materials, for example, it can also be used as a membrane used in a filtration device, etc. There are no particular restrictions on the functional layer that can be used in combination with the polyimide resin porous membrane in the present invention, and for example, a functional layer having a chemical function or a physicochemical function such as a nylon membrane, a polytetrafluoroethylene (PTFE) membrane, a tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA) membrane, or a membrane obtained by modifying these membranes can be cited.

[0166] In the liquid purification method of the present invention, the polyimide resin porous membrane can be used in the form of a filter medium such as a metal filter used in the field of semiconductor manufacturing, or in the form of a laminate containing the filter medium and other filter materials, or in the form of a filter. As a filter, there is no particular restriction. In the filter, the polyimide resin porous membrane can be configured in a manner that the supply liquid and the filtrate intersect. Regarding the relationship with the liquid flow path, it can be configured in parallel with the flow path, or it can be configured in a manner that intersects with the flow path. In order to separate the supply liquid from the filtrate, the liquid can be appropriately sealed in the area before and after the polyimide resin porous membrane passes. For example, as a sealing method, the polyimide resin porous membrane in the present invention can be processed by light (UV) curing-based bonding or heat-based bonding (including bonding based on the anchor effect (hot melting, etc.)) or bonding using an adhesive, as needed, or the polyimide resin porous membrane in the present invention can be bonded to other filter materials (filters) by, for example, an assembly method, and these polyimide resin porous membranes can be further arranged in an outer container formed of a thermoplastic resin such as polyethylene, polypropylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), polyether sulfone (PES), polyimide, polyamide-imide, etc.

[0167] Regarding the filter medium as the third aspect of the present invention, a filter medium formed of a polyimide and / or polyamideimide porous membrane used in the liquid purification method of the present invention, and a filtration device including a polyimide and / or polyamideimide porous membrane are also one of the present invention.

[0168] The liquid purification method of the present invention can be suitably used to remove metals contained in the above-mentioned chemical solution used in the semiconductor manufacturing field. As metals, the removal rate of iron and zinc is particularly high. Regarding the metal removal rate described later, for iron, it can be, for example, 90% or more, preferably 95% or more, more preferably 97% or more, and even more preferably 98% or more. For zinc, it can be, for example, 45% or more, preferably 50% or more, and more preferably 60% or more. For zinc contained in pure water, it can be, for example, 80% or more, preferably 85% or more, and more preferably 90% or more. In the case of using a polyimide resin porous membrane that has undergone an imide bond ring-opening process, it can also be, for example, 95% or more, and preferably 98% or more. The upper limit of the metal removal rate is preferably higher, so it is not particularly set, but for iron, for example, the upper limit is less than 100%, usually, when the liquid is an organic solvent, it can be 99.5% or less, when the liquid is pure water, it can be 99% or less. For zinc, for example, it can be 100% or less, and sometimes it can be 99% or less depending on the situation.

[0169] In addition, for the liquid purification method of the present invention, when it is used to remove impurities such as metals contained in the above-mentioned liquid medicine used in the semiconductor manufacturing field, the flow rate of the liquid medicine and other fluids can also be maintained at a high level to remove impurities. As the flow rate at this time, there is no particular restriction. For example, the flow rate of pure water when pressurized at 0.08MPa at room temperature is 1ml / minute or more, preferably 3ml / minute or more, more preferably 5ml / minute or more, and particularly preferably 10ml / minute or more. The upper limit is not particularly limited, for example, it can be 50ml / minute or less. For the liquid purification method of the present invention, the removal rate of impurities can be maintained at a high level while the flow rate is maintained at a high level as described above.

[0170] In the method for purifying a liquid of the present invention, if a polyimide-based resin porous membrane having polyimide and / or polyamide-imide as the main component is used, the flow rate of a fluid such as a drug solution can be maintained at a high level, and the method can also be suitably applied to a circulation-type purification (while a liquid such as a drug solution is continuously circulated, the polyimide-based resin porous membrane is allowed to pass through). The polyimide-based resin porous membrane of the present invention also has excellent mechanical properties such as stress and elongation at break. For example, the stress can be preferably 10 MPa or more, more preferably 15 MPa or more, and further preferably 15 to 50 MPa. In addition, the elongation at break can be, for example, 10% GL or more, and preferably 15% GL or more. The upper limit of the elongation at break can be, for example, 50% GL, preferably 45% GL, and more preferably 40% GL. When the porosity is reduced, the elongation at break tends to increase.

[0171] [Method for producing chemical solution or cleaning solution]

[0172] The second method for producing a liquid or cleaning solution of the present invention uses the first method for purifying a liquid. The first method for purifying a liquid of the present invention is a method having an excellent purification effect as described above, and therefore, the second method for producing a liquid using the liquid purification method can produce a liquid or cleaning solution having a reduced impurity content.

[0173] Example

[0174] Hereinafter, the present invention will be described in more detail with reference to Examples, but the scope of the present invention is not limited to these Examples.

[0175] In the examples and comparative examples, the following tetracarboxylic dianhydride, diamine, polyamic acid, polyamide-imide, organic solvent, dispersant and microparticles were used. It should be noted that the particle size distribution index (d25 / 75) of silica (1) was about 3.3, and the particle size distribution index (d25 / 75) of silica (2) was about 1.5.

[0176] ·Tetracarboxylic dianhydride: pyromellitic dianhydride

[0177] Diamine: 4,4'-diaminodiphenyl ether

[0178] Polyamic acid solution: reaction product of pyromellitic dianhydride and 4,4'-diaminodiphenyl ether (solid content: 21.9% by mass (organic solvent: N,N-dimethylacetamide))

[0179] Organic solvent (1): N, N-dimethylacetamide (DMAc)

[0180] Organic solvent (2): γ-butyrolactone

[0181] Dispersant: Polyoxyethylene secondary alkyl ether dispersant

[0182] · Microparticles: Silica (1): Silica with an average particle size of 700 nm

[0183] Silicon dioxide (2): Silicon dioxide with an average particle size of 300 nm

[0184] Etching solution (1):

[0185] Methanol: water (mass ratio 3:7) mixed solution of 1.1 mass% NaOH

[0186] Etching solution (2):

[0187] A 1.0 mass% solution of tetramethylammonium hydroxide (TMAH) in a mixture of methanol and water (mass ratio 4:6)

[0188] <Examples 1 to 4> Porous Polyimide Membrane

[0189] [Preparation of Silica Dispersion]

[0190] To a mixture of 23.1 parts by mass of an organic solvent (1) and 0.1 parts by mass of a dispersant was added 23.1 parts by mass of silica (1) or silica (2) having an average particle size shown in Table 1, and the mixture was stirred to prepare a silica dispersion.

[0191] [Preparation of varnish]

[0192] To 41.1 parts by mass of the polyamic acid solution, 42.0 parts by mass of the silica dispersion obtained in "Preparation of silica dispersion" was added, and then organic solvents (1) and (2) were added respectively so that the solvent composition of the entire varnish became organic solvent (1): organic solvent (2) = 90:10, and stirred to prepare a varnish. It should be noted that the volume ratio of polyamic acid to silica in the obtained varnish was 40:60 (mass ratio was 30:70).

[0193] [Film formation of unfired composite film]

[0194] Using an applicator, a film of the above-mentioned varnish was formed on a polyethylene terephthalate (PET) film as a substrate. Pre-baking was performed at 90°C for 5 minutes to produce an unfired composite film with a film thickness of 40 μm. The unfired composite film was immersed in water for 3 minutes, and then passed between two rollers to pressurize the unfired composite film. At this time, the roller extrusion pressure was 3.0 kg / cm 2 The roll temperature was 80° C. and the moving speed of the unsintered composite film was 0.5 m / min. The unsintered composite film was peeled off from the substrate to obtain an unsintered composite film.

[0195] [Imidization of unfired composite film]

[0196] The unfired composite film was subjected to a heat treatment (fired) at the temperature described in Table 1 for 15 minutes each, thereby imidization was performed to obtain a polyimide-fine particle composite film.

[0197] [Formation of porous polyimide film]

[0198] The polyimide-microparticle composite membrane obtained above was immersed in a 10% HF solution for 10 minutes to remove the microparticles contained in the membrane, and then washed with water and dried to obtain a porous polyimide membrane.

[0199] [Chemical etching]

[0200] In Examples 1 and 2, as an imide bond ring-opening step, the porous polyimide membrane was immersed in a chemical etching solution (1) for 2 minutes to perform an imide bond ring-opening step to obtain a porous polyimide membrane.

[0201] In Examples 3 and 4, chemical etching as an imide bond opening step and subsequent re-firing were not performed.

[0202] <Comparative Examples 1 and 2> Porous membranes of other resins

[0203] As Comparative Example 1, a porous membrane made of polyamide (nylon) (pore size: about 10 nm or less, membrane thickness about 75 μm) was prepared, and as Comparative Example 2, a porous membrane made of polyethylene (pore size: about 10 nm or less, membrane thickness about 50 μm) was prepared.

[0204] <Evaluation>

[0205] The following evaluations were performed on each porous membrane prepared as described above.

[0206] [Imidization rate]

[0207] The porous membranes subjected to chemical etching as the imide bond ring-opening step were calcined at the temperature shown in Table 1 for 15 minutes as described above, and then the value obtained by dividing the area of ​​the peak indicating the imide bond measured by the Fourier transform infrared spectroscopy (FT-IR) apparatus by the area of ​​the peak indicating benzene measured by the FT-IR apparatus was obtained (the aforementioned X2). The value obtained by measuring the porous membranes made of the same varnish as the respective porous membranes (a membrane that substantially completed the imidization reaction and was not subjected to chemical etching) (the aforementioned X1) was obtained to obtain the unchanged rate (%). The unchanged rates and the values ​​of X2 are respectively recorded in Table 1.

[0208] [Stress and elongation at break]

[0209] Each prepared porous membrane was cut into a size of 3 cm×3 mm to obtain a long strip sample. The stress at break (MPa; tensile strength) and elongation at break (%GL) of the sample were evaluated using EZ Test (manufactured by Shimadzu Corporation). The results are shown in Table 1.

[0210] [Metal removal rate and flow rate]

[0211] A circle with a diameter of 47 mm was cut from each prepared porous membrane, used as a filter material, and placed in a housing to allow 200 mL of isopropanol to pass through. Then, for a liquid containing metal impurities prepared by adding iron and zinc to pure water (DIW) or propylene glycol monomethyl ether (PGME), after measuring the contents (A) of iron and zinc in the liquid, the liquid was passed while nitrogen pressurization was performed at 0.08 MPa, and the time spent by each liquid containing metal impurities was measured to obtain the flow rate (ml / minute). The results are shown in Table 1.

[0212] The contents of iron and zinc (B) in the liquid after the liquid was passed were measured, and the value represented by the following formula was taken as the metal removal rate (%), and the evaluation was performed according to the following criteria.

[0213] (AB) / B×100

[0214] However, the polyethylene porous membrane was broken at 0.08 MPa and the metal removal rate could not be calculated. Therefore, the metal removal rate (%) when the liquid was passed under nitrogen pressure of 0.04 MPa is shown as a reference value.

[0215] [Gurley breathability]

[0216] For each of the above porous films, a sample having a thickness of about 40 μm was cut into 5 cm squares. The time for 100 ml of air to pass through the sample was measured using a Gurley densometer (manufactured by Toyo Seiki Co., Ltd.) in accordance with JIS P 8117. The results are shown in Table 1.

[0217] [Solvent resistance]

[0218] Test pieces of each polyimide porous membrane were prepared in the same manner as in Examples 1 to 4, and the effect of immersion in butyl acetate and cyclohexanone for 24 hours at room temperature was confirmed. Specifically, the reduction rate of the tensile strength after immersion was determined when the tensile strength before immersion was taken as 100%. The tensile strength was measured in the same manner as the above-mentioned stress at break. For any solvent, the reduction rate of the tensile strength was less than 1%, and it was confirmed that there was almost no effect caused by the solvent.

[0219]

[0220] As can be seen from Table 1, the metal removal rates in the examples are generally better than those in the comparative examples, and in particular, are much better than those in the comparative example 1 using a nylon porous membrane. In addition, the metal removal rates of the examples are equal to or higher than those of the polyethylene porous membrane of the comparative example 2 in which the pressurization conditions are reduced, and thus it can be confirmed that the examples are membranes with high metal removal rates.

[0221] In each example, the flow rate of DIW was equal to or higher than that of Comparative Example 1, and the flow rate of PGME was faster than that of Comparative Example 2, and it was confirmed that the flow rate range was applicable to both water-based and solvent-based systems.

[0222] Each embodiment has a high removal rate and an appropriate flow rate due to a thinner membrane thickness than the comparative example. Therefore, when the polyimide resin porous membrane is used as a filter medium or a filter device, the medium (media) can be made thinner and the device can be miniaturized. When the polyimide resin porous membrane is processed into a pleated shape, multiple pleats can also be formed. Therefore, a filter device with higher removal performance can be made.

[0223] It is understood from Examples 1 and 2 and Examples 3 and 4 that when chemical etching is performed as an imide bond opening step, the metal removal rate in pure water and PGME is improved.

[0224] Regarding the metal removal rates of the various examples, it can be seen that in the case of pure water, the metal removal rates of Fe and Zn are approximately the same, but in the case of chemical etching as an imide bond opening process, the metal removal rate of Zn is slightly higher than that of Fe, and in the case of not performing chemical etching as an imide bond opening process, the metal removal rate of Fe is instead slightly higher than that of Zn.

[0225] It is understood from Examples 1 and 3 and Examples 2 and 4 that when the imidization rate is reduced by chemical etching as the imide bond opening step, the flow rate can be increased while maintaining a good metal removal rate (adsorption rate).

[0226] From Comparative Example 1 using a nylon porous membrane, it is found that although the flow rate of PGME in particular can be increased, the metal removal rate is very low.

[0227] In Comparative Example 2 using a porous polyethylene membrane, as described above with respect to [flow rate], the membrane ruptured under nitrogen pressure of 0.08 MPa, and therefore, the metal removal rate of Fe in PGME shown in Table 1 is the metal removal rate of Fe under nitrogen pressure of 0.04 MPa, and therefore, the flow rate became slower than 2 ml / min. It is presumed that due to the slow flow rate, Fe removal was performed under more favorable conditions compared to the other embodiments performed at a fast flow rate.

[0228] As described above, it is found that it is impossible to simultaneously achieve a high flow rate and a high metal removal rate in Comparative Example 1 using a conventional nylon porous membrane and Comparative Example 2 using a polyethylene porous membrane.

[0229] In addition, according to the solvent resistance test, it can be confirmed that the polyimide porous membrane has resistance to butyl acetate and cyclohexanone. Generally, for butyl acetate, polyethylene filters are avoided, and for cyclohexanone, polyethylene filters and nylon filters are avoided. Therefore, when these solvents are to be purified, the polyimide porous membrane can be used as a filter medium.

[0230] <Example 5>

[0231] A filtration device having the same polyimide porous membrane as in Example 2 was prepared.

[0232] <Example 6>

[0233] A polyimide porous membrane was obtained in the same manner as in Example 2 except that the etching solution (2) was used as the chemical etching solution. The imidization ratio of the obtained polyimide porous membrane of X2 was 1.51. The Gurley air permeability was 230 seconds. A filtration device having the polyimide porous membrane was prepared.

[0234] <Comparative Example 3>

[0235] A filtration device (manufactured by Pall Corporation, Dispo) having a porous membrane (pore size: about 20 nm) made of polyamide (nylon) was prepared.

[0236] <Evaluation>

[0237] The following evaluations were performed on each of the filtration devices prepared in Examples 5 and 6 and Comparative Example 3 using the liquid flow objects shown in Table 2.

[0238] [Metal removal rate]

[0239] Prepare the following resin solution and chemically amplified resist composition, and evaluate the metal removal rate. The metal removal rate is calculated using the same formula as the above metal removal rate evaluation. The iron content of the resin solution or chemically amplified resist composition before passing the liquid is recorded as (A), and the iron impurity content of the liquid after passing the liquid through each prepared filter device is recorded as (B). In any case, the filtering conditions are: room temperature and a filtering pressure of 1.0 kgf / cm 2 (9.8N / cm 2 ).

[0240] ·Resin solution (1) to (3)

[0241] The following polymer compounds (1) to (3) were respectively dissolved in a mixed solvent of propylene glycol monomethyl ether acetate:propylene glycol monomethyl ether=60:40 (mass ratio) to obtain a 4 mass % resin solution.

[0242] [Chemical formula 5]

[0243]

[0244] [Mw: 7000, l:m:n=40:40:20 (molar ratio)]

[0245] [Chemical formula 6]

[0246]

[0247] [Mw: 7000, l:m:n=40:40:20 (molar ratio)]

[0248] [Chemical formula 7]

[0249]

[0250] [Mw: 7000, l:m:n:o:p=35:27:18:13:7 (molar ratio)]

[0251] Chemically amplified resist composition (1)

[0252] 100 parts by mass of the polymer compound (1), 3.6 parts by mass of the acid generator (1) and 0.4 parts by mass of tri-n-octylamine were mixed with a mixed solvent of propylene glycol monomethyl ether acetate:propylene glycol monomethyl ether=60:40 (mass ratio) so that the solid content concentration of the polymer compound (1) became about 7%, thereby preparing a chemically amplified resist composition (hereinafter sometimes referred to as "resist (1)").

[0253] [Chemical formula 8]

[0254]

[0255] [Table 2]

[0256]

[0257] As can be seen from Table 2, in each of the Examples, even when the liquid passing object is a resin solution or a resist composition, the metal removal rate is far superior to that of the Comparative Example.

Claims

1. A method for purifying a liquid, comprising the following steps: Using differential pressure, a part or all of the liquid is allowed to permeate from one side of the polyimide porous membrane having communicating pores to the other side; in, The polyimide porous membrane is a polyimide porous membrane obtained by a process of forming carboxyl groups and / or salt-type carboxyl groups from a part of the imide bonds, and the imidization rate is 1.2 or more and less than 1.5, and the imidization rate is a value represented by a value obtained by dividing the area of ​​the peak representing the imide bonds measured by a Fourier transform infrared spectroscopy (FT-IR) device by the area of ​​the peak representing benzene measured by the FT-IR device, wherein when the varnish used to form the porous membrane contains polyamic acid, it is considered that the imidization reaction has been substantially completed in the calcining process, The interconnected pores include a structure formed by interconnected nearly spherical pores with an average spherical diameter of 50 to 2000 nm. Using the porous membrane, part or all of the impurities including elements that are solid at room temperature contained in the liquid are removed from the liquid. The element is at least one selected from the group consisting of metal elements and semi-metal elements, The metal element is at least one selected from the group consisting of alkali metals, alkaline earth metals, transition metals belonging to Groups 3 to 11 of the periodic table, and metals belonging to Groups 12 to 15 of the periodic table, and the alkali metal is Li or K.

2. The method for purifying a liquid according to claim 1, wherein: The differential pressure is applied by at least one selected from the group consisting of a liquid flow pressure, a vacuum, and a positive pressure using an inert gas or a non-reactive gas.

3. The method for purifying a liquid according to claim 1 or 2, wherein: The communicating holes include communicating holes with a hole diameter of 1 to 200 nm.

4. The method for purifying a liquid according to claim 1 or 2, wherein: The nearly spherical hole further has a concave portion on the inner surface.

5. The method for purifying a liquid according to claim 1 or 2, wherein: The liquid is a chemical solution or a cleaning solution used in semiconductor manufacturing.

6. A method for producing a drug solution or a cleaning solution, using the method for purifying a liquid according to any one of claims 1 to 5. 7 . A filter medium formed of the polyimide porous membrane used in the method for purifying a liquid according to claim 1 . 8 . A filtration device comprising the porous polyimide membrane used in the method for purifying a liquid according to claim 1 .

Citation Information

Patent Citations

  • JP1971037476Y1

  • Cross-linked polyimide membranes

    CN101678286A

  • Preparation method of solvent resistant polyimide nanofiltration film

    CN101785977A

  • Polyimide containing porphyrin as well as preparation method and application thereof

    CN101948569A

  • High-temperature resistance polyamide composite membrane and preparation method thereof

    CN103111195A